2013
DOI: 10.1073/pnas.1213713110
|View full text |Cite
|
Sign up to set email alerts
|

Mouse marginal zone B cells harbor specificities similar to human broadly neutralizing HIV antibodies

Abstract: A series of potent, broadly neutralizing HIV antibodies have been isolated from B cells of HIV-infected individuals. VRC01 represents a subset of these antibodies that mediate neutralization with a restricted set of IGHV genes. The memory B cells expressing these antibodies were isolated years after infection; thus, the B-cell subpopulation from which they originated and the extent of participation in the initial HIV antibody response, if any, are unclear. Here we evaluated the frequency of anti-gp120 B cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…In humans, the anti-gp160 antibody response to HIV-1 has been shown to predominantly arise from poly-/autoreactive mature B cells ( Mouquet et al, 2011 ; Mouquet and Nussenzweig, 2012 ). In mice, transitional, anergic and marginal zone B cell subpopulations have all been characterized to express a poly-/autoreactive antibody repertoire ( Chen et al, 1997 ; Carey et al, 2008 ), and we previously reported that marginal zone B cells from naive wild-type B6 mice often express a gp120-reactive antibody receptor that also displays autoreactivity toward nuclear antigens ( Pujanauski et al, 2013 ). Which of these B cell populations, if any, is responsible for tier 2 HIV-neutralizing activity and whether Env-elicited HIV-1–neutralizing B cells can develop into memory B cells remains to be determined but can be addressed with mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the anti-gp160 antibody response to HIV-1 has been shown to predominantly arise from poly-/autoreactive mature B cells ( Mouquet et al, 2011 ; Mouquet and Nussenzweig, 2012 ). In mice, transitional, anergic and marginal zone B cell subpopulations have all been characterized to express a poly-/autoreactive antibody repertoire ( Chen et al, 1997 ; Carey et al, 2008 ), and we previously reported that marginal zone B cells from naive wild-type B6 mice often express a gp120-reactive antibody receptor that also displays autoreactivity toward nuclear antigens ( Pujanauski et al, 2013 ). Which of these B cell populations, if any, is responsible for tier 2 HIV-neutralizing activity and whether Env-elicited HIV-1–neutralizing B cells can develop into memory B cells remains to be determined but can be addressed with mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Another likely possibility is that the neutralizing antibodies observed arise from broadly reactive marginal zone B cells through affinity maturation. Mouse marginal zone B cells have recently been shown to harbor specificities similar to those of human bNAbs (10).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the mature B cell repertoire likely contains weakly HIV-1 reactive B cell clones, as well as some strongly reactive B cell clones that escape tolerance checkpoints or assume an anergic state. Recent evidence suggests that the mature B cell repertoire in both mice and humans contains clones that bind HIV-1 Env and are often polyreactive (9,10). Thus, in principle, it should be possible to design vaccines targeting HIV envelope-specific B cells that can serve as precursors for anti-HIV-1 bNAbs (7,11).…”
mentioning
confidence: 99%
“…In addition, a large proportion of other B-cell subsets (i.e. MZ, B-1) (71,72), recently shown to harbor specificities resembling those of some BnAbs (73) also exhibit in vitro poly-/autoreactivity. “False negatives” can result from technical inter or intra-assay variation between laboratories.…”
Section: Examining the Extent To Which Bnab Lineages Are Under Host Tmentioning
confidence: 99%